2018
DOI: 10.1093/brain/awy033
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate proteoglycans as novel drivers of leucocyte infiltration in multiple sclerosis

Abstract: Multiple sclerosis presents with profound changes in the network of molecules involved in maintaining central nervous system architecture, the extracellular matrix. The extracellular matrix components, particularly the chondroitin sulfate proteoglycans, have functions beyond structural support including their potential interaction with, and regulation of, inflammatory molecules. To investigate the roles of chondroitin sulfate proteoglycans in multiple sclerosis, we used the experimental autoimmune encephalomye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 57 publications
(73 reference statements)
9
68
0
Order By: Relevance
“…In the inflamed postcapillary venules of EAEafflicted mice, leukocytes that have migrated out of the vessel lumen across the endothelial cell layer accumulate within the perivascular space between the endothelial and parenchymal basement membranes (2,3); the collective structure is referred to as a perivascular cuff ( Figure 1A). Previous studies have emphasized that leukocytes within the perivascular space have remarkable functions, including antigen presentation (6) and secretion of MMPs (24), and these actions probably have high metabolic demands. In support of this, we observed that the expression of LDHA, a key glycolytic enzyme involved in the conversion of pyruvate to lactate, was strongly upregulated in the perivascular cuff on day 16 (D16, a period of prominent clinical disability) in the white matter of the cerebellum, a CNS region where perivascular cuffs are clearly demarcated in EAE ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the inflamed postcapillary venules of EAEafflicted mice, leukocytes that have migrated out of the vessel lumen across the endothelial cell layer accumulate within the perivascular space between the endothelial and parenchymal basement membranes (2,3); the collective structure is referred to as a perivascular cuff ( Figure 1A). Previous studies have emphasized that leukocytes within the perivascular space have remarkable functions, including antigen presentation (6) and secretion of MMPs (24), and these actions probably have high metabolic demands. In support of this, we observed that the expression of LDHA, a key glycolytic enzyme involved in the conversion of pyruvate to lactate, was strongly upregulated in the perivascular cuff on day 16 (D16, a period of prominent clinical disability) in the white matter of the cerebellum, a CNS region where perivascular cuffs are clearly demarcated in EAE ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…We tested whether LDHA modulates proinflammatory activities and aids leukocyte infiltration across the BBB. We resorted to macrophages in culture, as these cells typically constitute more than 80% of leukocytes within perivascular cuffs at peak EAE (24). When bone marrow-derived macrophages (BMDMs) were exposed to a nontoxic (20 μM; Figure 2A) concentration of a small-molecule-specific LDHA inhibitor, 3-dihydroxy-6-methyl-7-(phenylmethyl)-4-propylnaphthalene-1-carboxylic acid (FX11) (12, 31), we detected a significant decrease in secreted lactate levels as compared with LPS-treated cells ( Figure 2B), indicating a decrease in LDHA function.…”
Section: Enhanced Glycolytic Metabolism Supports Transmigration Of Brmentioning
confidence: 99%
“…Versican is essential during development (76,77) and it is now becoming apparent that it is an important component of the tissue inflammation caused by infection and tissue injury (10). Versican accumulates as part of the early inflammatory response in a number of human diseases often associated with the invasion of leukocytes including those in the vascular system (10,40,(78)(79)(80)(81)(82)(83)(84), lung (5,6,60,77,(85)(86)(87)(88)(89), brain and spinal cord (53,(90)(91)(92), intestine (93)(94)(95)(96), heart (97), liver (63), skin (98,99), eye (100, 101), pancreatic islets (102), and many different forms of cancer [reviewed in (103)(104)(105)]. The accumulation of versican in these tissues is usually associated with other ECM components that bind versican, such as hyaluronan (106,107), link protein, TSG-6, IαI, and CD44 (95, 96, 108-111) (Figure 1).…”
Section: Versican: a Component Of The Inflammatory Responsementioning
confidence: 99%
“…These cable-like structures contain hyaluronan, versican, TSG-6, and IαI that bind different subsets of leukocytes (93,94,112,(114)(115)(116)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147). Such structures have not only been found in vitro, but also in diseased tissues, such as in atherosclerosis (10,84), inflammatory bowel disease (IBD) (94), and in brain and spinal cord injury (53,91). Further studies are needed to determine the contribution of each of the components in the complex on leukocyte phenotype.…”
Section: Versican: Interplay With Leukocytesmentioning
confidence: 99%
“…We observed a major reduction in CS GAG signals across a range of molecular weights in Chsy1 skt mice compared to control mice ( Figure 5E), suggesting that various CSPGs are generally affected in this mouse model. To examine whether CSPG core protein expression is affected, we performed Western blotting for some of the major CSPG core proteins in the central nervous system including aggrecan, brevican, and versican (Stephenson et al 2018) on brain lysates that were pretreated with the chondroitinase ABC enzyme. We did not find significant differences in signals for these core proteins ( Figure 5E), suggesting that while these core proteins are present, their CS modification is disrupted by the Chsy1 skt mutation.…”
Section: The Chsy1 Gene Is Mutated In Skt Micementioning
confidence: 99%